2008
DOI: 10.3354/dao01966
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Marteilia refringens using nested PCR and in situ hybridisation in Chamelea gallina from the Balearic Islands (Spain)

Abstract: In the course of a histopathological survey performed to discover the cause of mass mortality of the striped clam Chamelea gallina in the Balearic Islands (Spain, Mediterranean Sea), we detected a Marteilia-like parasite in 3 clams. Molecular methods were applied to identify the parasite. DNA extracted from a paraffin block was used to carry out a PCR assay for Marteilia refringens detection based on a rDNA sequence of the parasite (the intergenic spacer of ribosomal genes, IGS). The nucleotide sequence of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2009
2009
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Two distinct sources of DNA were employed: (a) two paraffin blocks in whose histological sections infection by Marteilia sp. was diagnosed (accordingly with the methodology by López-Flores et al (2008); and (b)) tissues of pygmy mussels from sample B. The universal primers used are indicated in Table 1.…”
Section: Pathological Conditionmentioning
confidence: 99%
“…Two distinct sources of DNA were employed: (a) two paraffin blocks in whose histological sections infection by Marteilia sp. was diagnosed (accordingly with the methodology by López-Flores et al (2008); and (b)) tissues of pygmy mussels from sample B. The universal primers used are indicated in Table 1.…”
Section: Pathological Conditionmentioning
confidence: 99%
“…Subsequent studies have reinforced these findings, although the degree of affinity of M-type to mussels and O-type to oysters has not been analysed. Furthermore, the host range of M. refringens is clearly wider than O. edulis and M. edulis : both types being detected in Mytilus galloprovincialis (Novoa et al 2005 ; Balseiro et al 2007 ) and the M-type in clam Solen marginatus (López-Flores et al 2008 b ) and the mussel Xenostrobus securis (Pascual et al 2010 ) and, the O-type in the clam Chamelea gallina (López-Flores et al 2008 a ). Berthe et al ( 2004 ) point out that unidentified Marteilia isolates have also been observed in many bivalve species naturally present in the geographic range of M. refringens .…”
Section: Introductionmentioning
confidence: 99%
“…and Marteilioides spp. are the main focus of research (López-Flores et al 2008b). Based on molecular evidence, Marteilia spp.…”
mentioning
confidence: 99%